Construction of CoNiFe Trimetallic Carbonate Hydroxide Hierarchical Hollow Microflowers with Oxygen Vacancies for Electrocatalytic Water Oxidation. (1st June 2022) - Liu, Yihao; Chen, Guanyu; Ge, Riyue; Pei, Ke; Song, Chenxi; Li, Wenxian; Chen, Yingying; Zhang, Yuan; Feng, Lingyan; Che, Renchao
Abstract: It is of great challenge to design transition multimetallic carbonate hydroxides with delicate hollow features and defects for efficient electrolytic oxygen evolution reaction (OER). Here, a sequential self‐templating method to synthesize CoNiFe trimetallic carbonate hydroxide hierarchical hollow microflowers (CN‐xFe HMs) with oxygen vacancies (VO ) is reported. The synergistic merits of hollow structure, Fe substitution, and VO endow the CN‐xFe HMs with high active‐site exposure density and increased electrical conductivity. Specially, the optimized CN‐xFe HMs validate the excellent OER performance with an overpotential of 258 mV to drive 10 mA cm −2 and a Tafel slope of 48.7 mV dec −1 . Theoretical calculations reveal that Fe substitution and VO can synergistically regulate the electronic states to achieve near‐ideal adsorption/desorption capacity for oxygenated intermediates. Moreover, the successful synthesis of other six metals substituted CoNiM (M = Cu, Zn, Cr, Mo, Er and La) carbonate hydroxides provides a universal protocol to construct transition multimetallic electrocatalysts with hollow structures for gaining highly efficient energy conversion reactions. Abstract : Trimetallic CoNiM (M = Fe, Cu, Zn, Cr, Mo, Er, and La) carbonate hydroxide hierarchical hollow microflowers (CN‐xM HMs) are synthesized through a universal sequential self‐templating method. The large exposure intensity of active sites, high mass/charge transfer efficiency, and optimized adsorption free‐energy endow the CoNiFe electrocatalyst with superb alkaline oxidation evolution reaction performance.